GAMBARAN PENGETAHUAN PASANGAN USIA SUBUR TENTANG PENYAKIT GONORE DI DUSUN V DESA UJUNG RAMBUNG Kec. PANTAI CERMIN Kab.SERDANG BEDAGAI PERIODE 2015 - TISNILAWATI . (JURNAL ILMIAH KOHESI, 2018)
New cases of gonorrhea from year to year are increasing. According to the Annual Epidemiological Report 2013 by the European Disease Control and Prevention (ECDC) from 2007-2011 there was an increase in the number of gonorrhea cases by 19%. The purpose of this study was to determine the description of fertile age couples knowledge about gonorrhea disease in Hamlet V Ujung Rambung Village, Kec. Pantai Cermin Kab. Serdang Bedagai 2015 Period.The study was descriptive using primary data, the population in this study were all fertile couples in the hamlet V in Ujung Rambung Village, Kec. Pantai Cermin Kab. Serdang Bedagai for the 2015 period with 40 people. The sample in this study was all the population sampled in Hamlet V 40 people. The sampling technique is to use total sampling. Data analysis is discussed using existing library theory.From the results of research that has been done, it was found that at most 25 respondents (62.5%) had good knowledge. Based on age, most respondents were well-informed as many as 17 respondents (67.5%) in the age group 20-35 years.Based on the most knowledgeable education, there were 12 respondents (30%) in junior and senior high school education. Based on work, at most knowledgeable as many as 13 respondents (32.5%) at the IRT job. Based on the most well-informed source of information, 12 respondents (30%) in health workers.From the results of the study it can be concluded that the knowledge of fertile couples about Gonorrhea is the most knowledgeable. Therefore, it is expected that all couples of childbearing age be more knowledgeable especially about sexually transmitted diseases.